Assessment of student’s talent management in a corporate university - Hamidreza Ghomi (Management Science Letters, 2018)
The purpose of this study was to evaluate the student’s talent management of a corporate university in Iran by descriptive-analytic method. The statistical population of the study included all 2200 students of the university. Based on the estimated number at Morgan table, 202 respondents completed the survey instrument. The data collecting tool of the questionnaire was ascertained and its reliability was obtained 78 percent by Cronbach's alpha coefficient. Content validity of the tool was also veri-fied by the experts. For data analysis, the binomial test and Structural Equation Modeling (SEM) were used. The results show that none of the components of talent management (deployment and employment, career progression path, practical learning, performance management, knowledge sharing, self-development, training, appreciation and encouragement) in the studied university was in desire conditions. Other findings of the study also show that among organizational factors, compo-nents of “organizational culture”, “supervisor satisfaction”, “organizational dynamics”, “working environment conditions”, “colleagues”, “prestige and brand of the university” and “growth oppor-tunity” were influential on the students’ talent development. Also, the results of the data analysis show that among the components of job factors, the component of “person-job fitness” affects the development of students' talents.